Challenging Gender Norms: Anne Shirley’s Rejection of Femininity in Anne of Green Gables - Amanda Rania Yaasin; Imas Istiani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines how a nineteenth-century norm of femininity began to be questioned through the character of Anne Shirley in the novel Anne of Green Gables by L.M. Montgomery. Although this novel has been widely discussed in relation to childhood and moral development, Anne's behavior in this work is particularly noteworthy because it can be interpreted as a performative challenge to limited gender expectations. Using Judith Butler's theory of gender performativity, this study applies qualitative textual analysis to several selected scenes, using narrative description and interaction analysis between characters. The results show that Anne's expressiveness, intellectual ambition, and resistance to discipline can be seen as having a performative function that undermines social constructions of femininity. This study also shows that Anne's characterization operates in accordance with literary performances of gender resistance, rather than simply being an unconventional personality. These findings also contribute to the current feminist literary discussion on gender identity in classical texts.